PENGEMBANGAN MODEL PROBLEM BASED LEARNING DAN BLENDED LEARNING DALAM PEMBELAJARAN PEMANTAPAN KEMAMPUAN PROFESIONAL MAHASISWA - Enny Dwi Lestaringsih; Testiana Deni Wijayatiningsih (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2017)
This study is aimed at knowing the process of developing website media in the the teaching of â€œPemantapan Kemampuan Profesional Guru SDâ€ using problem based-learning and blended learning.The subjects of this study are the students taking â€œPemantapan Kemampuan Profesional Guru SDâ€ course. The development method used in this study is the one proposed by Hoge, Tondore, and Marelli.Â  The results showed that the media development application using website is appropriate to be used in the tutorial teaching in the classroom. It is proven by the validation result, that is the appropriateness between the indicator of concept, content, presentation, competence and the tutorial planning and syllabus, and also the tutorial materials of â€œPemantapan Kemampuan Profesionalâ€ course. There are also positive responds from the students after this website media is implemented. This also motivates the students in joining the tutorial. The tutors are expected to use the interesting teaching and learning model to improve the studentsâ€™ responds and motivation in joining the tutorial.Keywords: Blended Learning, development , Problem-based learning, Pemantapan Kemampuan Profesional course.